Estimate the parameters of Exponential-Rayleigh distribution, by using Bayesian method - Mohammed, Maral; Hassan, Iden (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In this paper, point estimation method for parameters α and λ of the parameters of the Exponential-Rayleigh distribution have been estimated by the use of a simulation technique by using two Bayesian estimation methods; the first Bayesian method of estimation consists of Lindely approximation estimation method and the second Bayesian estimation method consists Tierney and kadane approximation estimation method to estimate all the unknown parameters (α,λ) of Exponential-Rayleigh distribution. Comparisons between these two methods were made by employing mean squares error criterion. Applying a simulation technique with different sample sizes, these methods are being compared.